Molecular simulation insights into chemical-grafted EPDM for improving charge traps, moisture resistance, and pyrolysis tolerance - Gao, Mingze (2024)
This study explores and verifies the chemical modifications achieved by grafting 4-formylcyclohexyl heptanoate (FH) and 4-(2,5-dioxopyrrolidin-1-yl) cyclohexane-1-carbaldehyde (CC) onto ethylene propylene diene monomer (EPDM) elastomer, a prevalent dielectric material used for reinforced insulation in cable accessories. Employing a rigorous theoretical methodology combining first-principles calculations, molecular dynamics, and Monte Carlo molecular simulations, we elucidate the intricate effects of these chemical-graft modifications on the polymeric structure of EPDM to resist charge transport, moisture-aging, and thermal impact of partial discharge. Our investigation uncovers the emergence of both shallow and deep charge traps within the material, effectively mitigating electron avalanche breakdown. Additionally, we scrutinize the influence of two proposed organic species, acting as grafting agents, on several crucial properties of EPDM including water adsorption uptake, heat capacity, molecular thermal vibration, and polymer pyrolysis. These modifications substantially bolster EPDM’s resistance to high-temperature electrical breakdown and water thermodynamic adsorption, while also enhancing its thermal stability, rendering the proposed chemical-graft modifications an effective way and underling mechanisms for ameliorating electrical insulation performances of EPDM elastomer. Our findings highlight the significant potential of graft modification in molecular structures through comprehensive molecular simulations, offering valuable insights for advancing competent elastomeric polymers in cable accessory insulation.